REPUTATION OF JURGIS BALTRUŠAITIS IN THE BALTIC RUSSIAN PRESS IN THE 1920’S–1930’S - Лавринец, Павел (Literatūra, 2013)
This paper analyzes the reputation of Jurgis Baltrušaitis in the interwar Baltic Russian periodic press (Echo, Ponedelnik in Kaunas, Segodnya, Dlia Vas in Riga, and others). Its primary component was the of the Lithuanian diplomatic representative in Russia the activity of the, which in many ways was reflected in Russian newspapers’ messages, articles, and feuilletons. The diplomatic activity actualized Baltrušaitis as a poet and translator, and his creative work met some newspapers’ program provisions to promote Lithuanian culture. However, modest in scale and results, his actual work had little impact on the poet’s and diplomat’s literary reputation. The latter was formed by the earlier Russian poet’s and translator’s, one of the Russian symbolism creator’s merits. The nontrivial combination of a poet’s and a diplomat’s roles, an unusual situation at the Lithuanian and Russian cultural crossroads, the paradox of a Russian poet of Lithuanian origin was of special relevance for the national state building and a new political, civic, and ethnic identity formation era.